Status of Laboratory Biosafety and Biosecurity in Veterinary Research Facilities in Nigeria - Ismail Ayoade Odetokun; Afusat Toyin Jagun-Jubril; Bernard A. Onoja; Yiltawe Simwal Wungak; Ibrahim Adisa Raufu; Jessica Corron Chen (Elsevier, 2017)
Background: This study determined current status of laboratory biosafety in Nigerian veterinary research facilities. Methods: A questionnaire was developed to obtain information from researchers across Nigeria from July 2014 to July 2015. Information regarding demographics, knowledge of laboratory biosafety, availability and proper use of personal protective equipment (PPE), any priority pathogens researched, attitude on and use of standard laboratory practices, and biosafety awareness was obtained using a numeric scoring system. Data were analyzed with descriptive statistics, and univariate and multivariate logistic regression. Results: A total of 74 participants from 19 facilities completed the questionnaire. General knowledge scores ranged from 3 to 28 (out of 28 possible points), with 94.6% of respondents receiving low scores (scores < mean + 1 standard deviation). Very few (17.6%) reported availability or use PPE. Many participants (63.5%) reported no access to biosafety level (BSL)-1-3 facilities. None reported availability of a BSL-4 facility. Knowledge scores pertaining to biosafety management practices ranged from 0 to 14 (out of 14 possible points) with 47.3% of respondents receiving good scores (scores > mean + 1 standard deviation). Only 16.2% of respondents (from four facilities) reported having biosafety officers. Rabies virus was the most researched pathogen (31.1% of respondents). The majority (71.6%) were unaware of laws guiding biosafety. Researchers [odds ratio (OR) = 18.0; 95% confidence interval (CI): 1.63, 198.5; p = 0.023], especially in BSL-2 (OR = 258.5; 95% CI: 12.71, 5256; p < 0.001) facility of research institute (OR = 25.0; 95% CI: 5.18, 120.6; p < 0.001), are more likely to have adequate access to and properly utilize biosafety devices and PPE. Conclusions: Current knowledge of laboratory biosafety is limited except among a few researchers.